Safety and Feasibility of Antibiotic De-escalation in Critically Ill Children With Sepsis – A Prospective Analytical Study From a Pediatric ICU - Battula, Vasudha; Krupanandan, Ravi Kumar; Nambi, P. Senthur; Ramachandran, Bala (Frontiers in Pediatrics, 2021)
Introduction: De-escalation is the key to balance judicious antibiotic usage for life-threatening infections and reducing the emergence of antibiotic resistance due to antibiotic overuse. Robust evidence is lacking regarding the safety of antibiotic de-escalation in culture-negative sepsis. Materials and methods: Children admitted to the PICU during the first six months of 2019 with suspected infection were included. Based on the clinical condition, cultures and septic markers, antibiotics were de-escalated or continued at 48-72 hours. Outcome data like worsening of primary infection, acquisition of hospital-acquired infection, level of ICU support and mortality were captured. Results: Among the 360 admissions, 247 (68.6%) children received antibiotics. After excluding 92 children, 155 children with 162 episodes of sepsis were included in the study. 34 episodes were not eligible for de-escalation. Among the eligible group of 128 episodes, antibiotics were de-escalated in 95 (74.2%) and continued in 33 (25.8%).The primary infection worsened in 5 (5.2%) children in the de-escalation group and in 1 (3%) in non de-escalation group [Hazard ratio: 2.12 (95%CI: 0.39 - 11.46)]. There were no significant differences in rates of hospital-acquired infection, mortality, length of ICU stay amongst the groups. Blood cultures and assessment of clinical recovery played a major role in the de-escalation of antibiotics and the clinician’s hesitation to de-escalate in critically ill culture negative children was the main reason for not de-escalating among eligible children. Conclusion: Antibiotic de-escalation is a safe strategy to apply in critically ill children, even in those with negative cultures.